Learning in an organization as a strategy of the implementation of education policy in preschool education institution - Smilgienė, Jurgita; Gumuliauskienė, Aušrinė; Pivorytė, Rasa (Social Welfare: Interdisciplinary Approach, 2016)
The quality of education/training and the development of human resources are closely interrelated priorities of the education policy, the implementation of which plays a predominant role in the structure of the strategic management of educational institutions. The article deals with the problem of preschool education teachers’ learning in an organization in the context of the implementation of the strategic aims of education. The essence and importance of learning in an organization has been theoretically substantiated, referring to the data of the research the advantages of preschool education teachers’ learning in an organization, as well as the most effective ways of learning, its importance for the quality of education, particular fields of the activity of the institution
Keywords: preschool education teacher; learning in an organization; implementation of the education policy